Evaluation of the maternal deaths surveillance and response system at the health district level in Guinea in 2017 through digital communication tools - Tamba Mina Millimouno; Sidikiba Sidibé; Alexandre Delamou; Kéfilath Olatoyossi Akankè Bello; Basile Keugoung; Jean Paul Dossou; Abdoul Habib Beavogui; Bruno Meessen (BMC, 2019)
Abstract Background Reducing maternal mortality still remains a major challenge in low-income countries. This study aims to explore how digital communication tools can be used to evaluate the maternal deaths surveillance and response (MDSR) system at the health district level in Guinea. Methods A descriptive cross-sectional study was conducted, using an innovative digital approach called District.Team, from April to September 2017. This study targeted all 38 district medical officers in Guinea. In addition to district medical officers, the participation of health actors from regional and central levels were also expected in the online discussion forum. Data collected through the questionnaire were mixed and those from the online discussion forum were entirely qualitative. Results In total, 23 (61%) district medical officers (DMOs) participated in the study. Out of health districts (87%) which had updated guidelines and standards for the MDSR, 4 (20%) did not apply the content. In two health districts (8.7%), not all health facilities had maternal deaths notification forms. Three districts (13%) did not have maternal death review committees. In 2016, only half (50.2%) of reported maternal deaths were reviewed. The main recommendation formulated was related to quality of care. Other needs were also highlighted including continuous training of health care providers on emergency obstetric and neonatal care. Less than half (45%) of the review committee's recommendations were implemented. Six health districts (26.1%) did not have a response plan to reported maternal deaths and no district annual report on the MDSR was published in 2016. The weaknesses identified were, among others, insufficiency of human resources and lack of financial resources. Fifty-eight messages related to MDSR weaknesses and improvement solutions were posted in the online discussion forum by 28 participants (23 DMOs and 5 health actors from regional and central levels). Conclusion Digital tools can be used to assess the functioning of a system like maternal deaths surveillance and response. Moreover, the findings of the evaluation conducted will help stakeholders (starting from the health districts themselves) to design strategies and interventions for an effective MDSR.